2015
DOI: 10.3109/07388551.2015.1083943
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological applications of microbial bioconversions

Abstract: Modern research has focused on the microbial transformation of a huge variety of organic compounds to obtain compounds of therapeutic and/or industrial interest. Microbial transformation is a useful tool for producing new compounds, as a consequence of the variety of reactions for natural products. This article describes the production of many important compounds by biotransformation. Emphasis is placed on reporting the metabolites that may be of special interest to the pharmaceutical and biotechnological indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 119 publications
0
12
0
5
Order By: Relevance
“…Because the upstream production of l ‐phe already has been thoroughly studied and the production of l ‐phe has reached a high level, improvement of the conversion efficiency of the whole‐cell system to produce t ‐CA from l ‐phe is very important. As noted previously, t ‐CA and its derivatives showed remarkable inhibitory effects on PAL . From studies with CdPAL1 from Cistanche deserticola , t ‐CA was reported to have the strongest inhibitory effects with a Ki of 8 μmol L –1 .…”
Section: Discussionmentioning
confidence: 53%
“…Because the upstream production of l ‐phe already has been thoroughly studied and the production of l ‐phe has reached a high level, improvement of the conversion efficiency of the whole‐cell system to produce t ‐CA from l ‐phe is very important. As noted previously, t ‐CA and its derivatives showed remarkable inhibitory effects on PAL . From studies with CdPAL1 from Cistanche deserticola , t ‐CA was reported to have the strongest inhibitory effects with a Ki of 8 μmol L –1 .…”
Section: Discussionmentioning
confidence: 53%
“…3 Imobilização é um termo geral que descreve as muitas formas de fixação, encapsulamento ou aprisionamento de células ou enzimas em um suporte sólido. Especificamente, a imobilização de células íntegras representa uma forma particular de adesão celular baseada na habilidade de certos microrganismos de se fixarem em suportes sólidos por meio de ligações naturais ou físico-químicas.…”
Section: Imobilização De Células íNtegrasunclassified
“…[1][2] Adicionalmente, outros atributos benéficos da biotransformação incluem versatilidade reacional, especificidade, redução no número de etapas no processo e alto rendimento. 3 Diferente da fermentação, na biotransformação o biocatalisador transforma molé-culas precursoras pré-formadas (naturais ou sintéticas) em limitado número de etapas. Além disto, o produto formado não é limitado pelo metabolismo do biocatalisador.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Microbial transformation is the process by which fungus or bacteria are used to convert the substrate to a structurally related compound via one or a series of enzymatic reactions (Parshikov et al 2012;Perkins et al 2016). It is an excellent technique in modifying structure, enhancing efficacy and reducing toxicity of Traditional Chinese Medicine (TCM), due to its mild reaction conditions and convenient method (Cao et al 2015;Xie et al 2018).…”
Section: Introductionmentioning
confidence: 99%